2019
DOI: 10.1097/md.0000000000016976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of halitosis in adult patients after treatment with photodynamic therapy associated with periodontal treatment

Abstract: Rationale:Halitosis is an unpleasant odor that emanates from the mouth. Studies show halitosis returns in a week, after treatment with PDT. Probably, bacteria living in the periodontal sulcus could recolonize the dorsum of the tongue. Until nowadays, there are no study in adult population that associates halitosis and periodontal treatment with follow-up evaluation. The aim of this randomized, controlled, single-blinded clinical trial is to treat oral halitosis in healthy adults with photodynamic therapy (PDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fourteen studies were analysed in full text and one was excluded due to wrong study design [34]. Thus, six randomized clinical trials (RCTs) (reported in 13 references) [18,20,24,[34][35][36][37][38][39][40][41][42][43][44] were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were analysed in full text and one was excluded due to wrong study design [34]. Thus, six randomized clinical trials (RCTs) (reported in 13 references) [18,20,24,[34][35][36][37][38][39][40][41][42][43][44] were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%